Clusterin Plasma Concentrations Are Decreased in Sepsis and Inversely Correlated with Established Markers of Inflammation - Eray Yagmur; Samira Abu Jhaisha; Lukas Buendgens; Nadezhda Sapundzhieva; Jonathan F. Brozat; Philipp Hohlstein; Maike R. Pollmanns; Ger H. Koek; Ralf Weiskirchen; Christian Trautwein; Frank Tacke; Theresa H. Wirtz; et al. (Diagnostics, 2022)
Clusterin is a multifunctional protein that is recognized to mediate cellular stress response associated with organ failure, systemic inflammation, and metabolic alterations. The aim of this study was to determine the value of clusterin as a clinical biomarker in critical ill patients with or without sepsis. We analyzed clusterin plasma concentrations in 200 critically ill patients (133 with sepsis, 67 without sepsis) on admission to the medical intensive care unit (ICU). The results were compared with 66 healthy controls. Clusterin plasma concentration was significantly elevated in critically ill patients compared to healthy subjects. Clusterin levels were significantly higher in non-septic ICU patients than in patients with sepsis. Clusterin correlated inversely with routinely used biomarkers of inflammatory response. Furthermore, clusterin levels were higher in ICU patients with pre-existing obesity and type 2 diabetes. Clusterin was not associated with disease severity, organ failure, or mortality in the ICU. This study highlights significantly elevated clusterin levels in critically ill patients, predominantly in non-sepsis conditions, and associates circulating clusterin to inflammatory and metabolic dysfunctions.